Corporate Communications: Comparing Executives' Private and Public Statements - Fiol, C. Marlene (Academy of Management Journal, 1995)
People frame and make sense of their worlds through the use of cognitive categories, which researchers can only indirectly access. Public corporate statements are easily accessible and comparable across companies and over time, but it is unclear to what extent such statements reflect organization members' cognitive categorizations. This study is the first to directly compare executives' public and private statements to explore whether and along what dimensions public statements reflect internal company communications. Comparisons of internal and external documents generated by the forest products industry over ten years revealed no significant correlations in the two sets of documents between executives' positive or negative evaluations of events and situations; however, the correlations between their perceptions of control were positive and significant.